Analysis of Binary Logistic Regression Model on Passenger Transportation Mode Selection Between Train and Bus on Malang-Blitar Route - Nabila, Nuzulul Laili; Abusini, Sobri; Sa'adah, Umu (Fakultas Teknik Universitas Brawijaya, 2025)
The transportation dynamics between Malang and Blitar, characterized by significant student and worker mobility, present a complex decision-making landscape for public transportation mode selection. This study employed binary logistic regression to analyze factors influencing passenger choices between trains and buses, utilizing a comprehensive survey of 100 respondents. The research revealed convenience as the most statistically significant factor in transportation mode selection, transcending traditional considerations such as ticket pricing. Despite 80 participants initially expressing a preference for trains, the predictive model suggested a potential scenario where 74% might ultimately choose buses. This counterintuitive finding highlights accessibility, service frequency, boarding ease, and overall travel comfort in transportation decision-making. By quantifying the probabilistic relationships between various variables, the study provides transportation planners with a sophisticated analytical tool for understanding passenger behavior. The findings underscore passengers' willingness to pay a premium for transportation modes offering greater flexibility and comfort, challenging conventional assumptions about cost-driven travel choices. The binary logistic regression model's insights provide valuable guidance for infrastructure development and service optimization in the Malang-Blitar transportation corridor, emphasizing the critical role of convenience in shaping transportation preferences.